Antiochia i Aleksandria – czy zawsze teologiczna polaryzacja? Problem transcendencji oraz immanencji Boga w teologii Cyryla Aleksandryjskiego i Jana Złotoustego - Zhukovskyy, Viktor (Vox Patrum, 2012)
Cyril of Alexandria did not treat the problem of God’s transcendence and immanence as extensively and profoundly as did John Chrysostom, due to the fact that the question was not as relevant in Cyril’s time as is was in the time of Chrysostom. However, the ideas of the latter are present in the writings of Cyril, who draws a distinction between the inner being of God and His work. This similarity can be traced in two main points. First, God in His essential nature surpasses everything. This inner life of God is above and beyond any knowledge and reach, any concept and reasoning. All that we know about the nature of God is that He acts in the world and this action is performed by the Father through the Son in the Spirit. Second, in order to outline God’s action, Cyril uses the terms „power” and „energy” indistinguishably. For both authors the method of antinomy is a primary system of coordinates in which they combine the two fundamentally opposite poles of God’s being: the transcendent and the immanent. So, in this point the Oriental Theological Schools of Alexandria and Antioch are internally consonant.